Single phase controller for automated stand by generator for low power applications using programmable logic controller (PLC) / Mohd Isran Che Mustapha - Che Mustapha, Mohd Isran (1994)
The project concerns with the design and development of A Programmable Logic Controller for Automated Single Phase Standby Generator for Low Power Applications The system developed shall be capable of providing back-up supply up to 600 VA during power failure. Basically, the generator generates the supply after the supply from TNB breakdown and degenerates after the supply is restored. The ladder diagram is developed and PLC is used as a controller for the system.